ANALYSIS OF MACHINE MAINTENANCE USING MARKOV CHAIN METHOD FOR REDUCING MAINTENANCE COST - Pratama, Setya Adi; Putra, Boy Isma (Universitas Nusantara PGRI Kediri, 2022)
PT. Steel Pipe Industry of Indonesia, Tbk. (SPINDO Unit IV) is a company engaged in manufacturing welding spiral pipe production. In 2019 there was an increase in maintenance costs compared to 2018, which in 2018 amounted to Rp 305.180.000 to Rp 329.940.000 in 2019, which mean an increase of Rp 24.760.000 or 8%. Based on those problems, the purpose of this study is to determine the policies that should implemented to reduce maintenace costs. The method used is markov chain method. By using the markov chain method, it can be determined the best policy that can lead to lower maintenance costs, whether preventive maintenance or corrective maintenance. So that the company can determine the best maintenance policy for the future. The result obtained from using the markov chain method for this research are that maintenance on the roller machine results in a saving of Rp 68.000.000 compared to initial maintenace costs, maintenance on the welding machine results in a saving of Rp 36.650.000 compared to initial maintenace costs, maintenance on the cutting machine results in a saving of Rp 54.020.000 compared to initial maintenace costs.